The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/s23063239
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement and Curriculum Learning for Off-Road Navigation of an UGV with a 3D LiDAR

Abstract: This paper presents the use of deep Reinforcement Learning (RL) for autonomous navigation of an Unmanned Ground Vehicle (UGV) with an onboard three-dimensional (3D) Light Detection and Ranging (LiDAR) sensor in off-road environments. For training, both the robotic simulator Gazebo and the Curriculum Learning paradigm are applied. Furthermore, an Actor–Critic Neural Network (NN) scheme is chosen with a suitable state and a custom reward function. To employ the 3D LiDAR data as part of the input state of the NNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The computer of Andabata employs an inertial measurement unit (IMU), with inclinometers, gyroscopes, and a compass, and a global navigation satellite system (GNSS) receiver with a horizontal resolution of 1 m included in its onboard smartphone for outdoor localization [36]. The main exteroceptive sensor for navigation is a custom 3D LiDAR sensor with 360°field of view built by rotating a 2D LiDAR [37].…”
Section: Outdoor Navigationmentioning
confidence: 99%
See 3 more Smart Citations
“…The computer of Andabata employs an inertial measurement unit (IMU), with inclinometers, gyroscopes, and a compass, and a global navigation satellite system (GNSS) receiver with a horizontal resolution of 1 m included in its onboard smartphone for outdoor localization [36]. The main exteroceptive sensor for navigation is a custom 3D LiDAR sensor with 360°field of view built by rotating a 2D LiDAR [37].…”
Section: Outdoor Navigationmentioning
confidence: 99%
“…Although waypoints for the UGV are calculated in the detected paths, reactivity is still necessary to avoid steep slopes and unexpected obstacles that are not visible on satellite images. Local navigation between distant waypoints has been implemented on Andabata with a previously developed actor-critic scheme, which was trained using reinforcement and curriculum learning [36].…”
Section: Outdoor Navigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Less common, but more relevant from that perspective, especially as computation capabilities increase, is the possibility of having deformable environmental objects and terrain [ 14 ]. Conducted analyses have shown that there are several simulators which offer extensive use case possibilities [ 15 , 16 , 17 , 18 ]. A solution commonly used in research is the MuJoCo [ 19 ].…”
Section: Introductionmentioning
confidence: 99%